ACOUSTIC WAVE PROPAGATION IN HIGH SCALE IMPEDANCE MISMATCH MEDIUMS - Awal, Md Rabiul; Jusoh, Muzammil; Yahya, Muhammad Syarifuddin; Rahman, Salisa Abdul; Dagang, Ahmad Nazri; Abdul Latiff, Nurul Adilah; Zakaria, Hidayatul Aini; Saat, Shakir (IIUM Engineering Journal, 2021)
A finite element analysis of acoustic propagation in a multilayered medium is presented in this paper. A circular transmitter (diameter 14 mm, thickness 3 mm) and a rectangular receiver (20×10×0.5 mm3) are set to detect the variations in the propagation pattern. A complex medium (70×40×60 mm3) composed of skin, fat, muscle, bone and liquid is designed in a simulated environment. A scale of frequencies (10 kHz to 2 MHz) is applied to trace the impact on the propagation pattern as well. It is found from the analysis that fat and liquid layers affect the acoustic propagation the most (-69 dB), which results in a significant drop in the received sound pressure level at the receiving end. Again, other than skin and fat layers, low frequencies (less than 1 MHz) are more beneficial in terms of sound pressure level. However, higher frequencies contribute to lower displacements at the receiving end, which will cause less power potential as well. ABSTRAK: Analisis elemen terhingga bagi penyebaran akustik dalam medium berlapis dibentangkan dalam kajian ini. Pemancar bulat (diameter 14 mm, ketebalan 3 mm) dan penerima segi empat tepat (20 × 10 × 0.5 mm3) diatur bagi mengesan perubahan pola penyebaran. Medium kompleks (70 × 40 × 60 mm3) yang terdiri daripada kulit, lemak, otot, tulang dan cecair direka dalam persekitaran simulasi. Skala frekuensi (10 kHz hingga 2 MHz) digunakan bagi mengesan corak penyebaran. Dapatan kajian menunjukkan bahawa lapisan lemak dan cecair mempengaruhi penyebaran akustik (-69 dB), yang mengakibatkan penurunan mendadak tahap penerimaan tekanan bunyi di hujung penerima. Selain lapisan kulit dan lemak, frekuensi rendah (kurang dari 1 MHz) adalah lebih berguna dari segi tahap tekanan suara. Walau bagaimanapun, frekuensi lebih tinggi menyebabkan kurang anjakan di hujung penerima, sekaligus mengurangkan potensi daya tenaga.